2021
DOI: 10.3389/fgene.2021.574196
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Functions and Prognostic Values of RNA Binding Proteins in Bladder Cancer

Abstract: Post-transcriptional regulation plays a leading role in gene regulation and RNA binding proteins (RBPs) are the most important posttranscriptional regulatory protein. RBPs had been found to be abnormally expressed in a variety of tumors and is closely related to its occurrence and progression. However, the exact mechanism of RBPs in bladder cancer (BC) is unknown. We downloaded transcriptomic data of BC from the Cancer Genome Atlas (TCGA) database and used bioinformatics techniques for subsequent analysis. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Nonetheless, all three IGF2BPs are highly expressed and function as independent prognostic factors in a variety of cancers, including lung cancer 89 , 90 , liver cancer 91 - 93 , breast cancer 94 , 95 , colorectal cancer 96 - 98 , pancreatic cancer 99 - 101 , prostate cancer 102 , bladder cancer 103 - 105 , thyroid cancer 106 - 108 , gastric cancer 109 , 110 , renal cell carcinoma 111 , ovarian cancer 112 , 113 , esophageal squamous cell carcinoma 114 , 115 , acute myeloid leukemia 116 . In addition to the high expression of the IGF2BPs itself, intercellular communication factors, such as tumor-secreted extracellular vesicles (EVs), can maintain the stability of IGF2BPs in cells to promote the development of cancer.…”
Section: The Oncogenic Role Of Igf2bps In Cancermentioning
confidence: 99%
“…Nonetheless, all three IGF2BPs are highly expressed and function as independent prognostic factors in a variety of cancers, including lung cancer 89 , 90 , liver cancer 91 - 93 , breast cancer 94 , 95 , colorectal cancer 96 - 98 , pancreatic cancer 99 - 101 , prostate cancer 102 , bladder cancer 103 - 105 , thyroid cancer 106 - 108 , gastric cancer 109 , 110 , renal cell carcinoma 111 , ovarian cancer 112 , 113 , esophageal squamous cell carcinoma 114 , 115 , acute myeloid leukemia 116 . In addition to the high expression of the IGF2BPs itself, intercellular communication factors, such as tumor-secreted extracellular vesicles (EVs), can maintain the stability of IGF2BPs in cells to promote the development of cancer.…”
Section: The Oncogenic Role Of Igf2bps In Cancermentioning
confidence: 99%
“…Furthermore, 12 prognostic RBP signatures have been explored, including CTIF, CTU1, DARS2, ENOX1, IGF2BP2, LIN28A, MTG1, NOVA1, PPARGC1B, RBMS3, TDRD1, and ZNF106. Studies found that MTG1, CTU1, and PPARGC1B gene expressions were related to optimistic prognoses in patients with BC, whereas high RBMS3, DARS2, ENOX1, IGF2BP2, ZNF106, CTIF, and NOVA1 gene expressions were related to pessimistic prognoses [ 15 ]. However, the exact and functional role of RBPs in the development and prognosis of BC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ZNF106 is an RNA binding protein involved in post-transcriptional regulation and insulin receptor signaling. Although germline variation in ZNF106 has not previously been associated with cancer risk, a recent study found it to be associated with worse urinary bladder cancer survival 32 .…”
Section: Discussionmentioning
confidence: 94%